Origins of magic: review of genetic and epigenetic effects. Issue 7633 (20th December 2007) - Ramagopalan, Sreeram V; Knight, Marian; Ebers, George C; Knight, Julian C
Abstract : Objective To assess the evidence for a genetic basis to magic. Design Literature review. Setting Harry Potter novels of J K Rowling. Participants Muggles, witches, wizards, and squibs. Interventions Limited. Main outcome measures Family and twin studies, magical ability, and specific magical skills. Results Magic shows strong evidence of heritability, with familial aggregation and concordance in twins. Evidence suggests magical ability to be a quantitative trait. Specific magical skills, notably being able to speak to snakes, predict the future, and change hair colour, all seem heritable. Conclusions A multilocus model with a dominant gene for magic might exist, controlled epistatically by one or more loci, possibly recessive in nature. Magical enhancers regulating gene expressionmay be involved, combined with mutations at specific genes implicated in speech and hair colour such as FOXP2 and MCR1.